Personal Loans (PINPRI) in the Review of Positive Law and Islamic Law - Dahyul Daipon; Basri Naali; Hamdani Hamdani; Fajrul Wadi; Hendri Hendri (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
This research aims to answer a problem regarding the practice of pinpri loans that have not been registered with the Financial Services Authority and how Islamic law reviews the reasons people make pinpri loans. The research method used is statute approach analysis and comparison. Based on the results of the study the practice of personal loans (pinpri) is a cash loan that has not been registered with the Financial Services Authority is the practice of lending through individuals and has not been registered or even licensed by the Financial Services Authority so that it can be said to be illegal and violates Financial Services Authority Regulation Number 77 / POJK.01 / 2016 concerning LPMUBTI, then in the practice of personal loans (pinpri) there are additional funds and have regulations that are not by the operational system listed in the cash loan rules. In terms of Islamic law, the reason why people practice personal loans (pinpri) is because of urgent needs, easy disbursement, and consumptive behavior, while this is contrary to the concept of Islamic law in qardh theory. Because in the practice of personal loans (pinpri) that have not been registered with the Financial Services Authority, several elements are not by Islamic law, namely usury, gharar, dharar, and zhulm so the law is haram and harms and brings mudharat to the community